Bank performance and economic growth : evidence from Granger panel causality estimations - Ferreira, Cândida (2013)
This paper provides empirical evidence on the causality relations between bank performance and economic growth in a panel including 27 European Union member-states from 1996 through to the onset of the 2008 financial crisis. Bank performance is represented not only by the Return on Assets (ROA) and Return on Equity (ROE) ratios but also by bank cost efficiency, measured through Data Envelopment Analysis (DEA). For economic growth, we consider not only the GDP per capita but also the gross fixed capital formation growth. Deploying a panel Granger causality approach, we confirm positive causality running from bank performance to economic growth. However, as regards the opposite causality, running from growth to bank performance, we conclude that economic growth positively contributes to the bank ROA and ROE ratios but not so certainly in the case of the DEA bank cost efficiency.